Do empowered women receive better quality antenatal care in Pakistan? An analysis of demographic and health survey data. - Muhammad Asim; Waqas Hameed; Sarah Saleem (PLoS ONE)
Introduction Quality antenatal care is a window of opportunity for improving maternal and neonatal outcomes. Numerous studies have shown a positive effect of women empowerment on improved coverage of maternal and reproductive health services, including antenatal care (ANC). However, there is scarce evidence on the association between women's empowerment and improved ANC services both in terms of coverage and quality. Addressing this gap, this paper examines the relationship between multi-dimensional measures of women empowerment on utilization of quality ANC (service coverage and consultation) in Pakistan. Methods We used Pakistan Demographic and Health Survey 2017-18 (PDHS) data which comprises of 6,602 currently married women aged between 15-49 years who had a live birth in the past five years preceding the survey. Our exposure variables were three-dimensional measures of women empowerment (social independence, decision making, and attitude towards domestic violence), and our outcome variables were quality of antenatal coverage [i.e. a composite binary measure based on skilled ANC (trained professional), timeliness (1st ANC visit during first trimester), sufficiency of ANC visits (4 or more)] and quality of ANC consultation (i.e. receiving at least 7 or more essential antenatal components out of 8). Data were analysed in Stata 16.0 software. Descriptive statistics were used to describe sample characteristics and binary logistic regression was employed to assess the association between empowerment and quality of antenatal care. Results We found that 41.4% of the women received quality ANC coverage and 30.6% received quality ANC consultations during pregnancy. After controlling for a number of socio-economic and demographic factors, all three measures of women's empowerment independently showed a positive relationship with both outcomes. Women with high autonomy (i.e. strongly opposed the notion of violence) in the domain of attitude to violence are 1.66 (95% CI 1.30-2.10) and 1.45 (95% CI 1.19-1.75) and times more likely to receive antenatal coverage and quality ANC consultations respectively, compared with women who ranked low on attitude to violence. Women who enjoy high social independence had 1.87 (95% CI 1.44-2.43) and 2.78 (95% CI 2.04-3.79) higher odds of quality antenatal coverage and consultations respectively, as compared with their counterparts. Similarly, women who had high autonomy in household decision making 1.98 (95% CI 1.60-2.44) and 1.56 (95% CI 2.17-1.91) were more likely to receive quality antenatal coverage and consultation respectively, as compared to women who possess low autonomy in household decision making. Conclusion The quality of ANC coverage and consultation with service provider is considerably low in Pakistan. Women's empowerment related to social independence, gendered beliefs about violence, and decision-making have an independent positive association with the utilisation of quality antenatal care. Thus, efforts directed towards empowering women could be an effective strategy to improve utilisation of quality antenatal care in Pakistan.